Journeys Home Research Report No. 5: Findings from Waves 1 to 5: Special Topics - Chigavazira, A; Moschion, J; Johnson, G; Scutella, R; Wooden, M; Tseng, Y (My University, 2014)
This research report, the fifth in our series, presents important findings from the first five waves of the Journeys Home(JH)study, which were conducted over a 2-year period between September 2011 and November 2013. JH is tracking a national sample of individuals exposed to high levels of housing insecurity. It employs much more rigorous sampling methods than ever previously used. In this report, after initially presenting an overview of fieldwork outcomes and housing transitions over the first five waves of the study, we investigate a selection of special topics in greater depth that are particularly pertinent to our population of interest. The five topics examined are: homelessness and employment; physical health and homelessness; social support and networks; first experiences of homelessness and initiation to substance use; and diet and food insecurity.
Journeys Home Research Report
Journeys Home Research Reports
Keywords: Social Capital -- Social support; Health -- Addictive behaviours; Homelessness; Health -- Physical; Employment; Homelessness -- Diet/Food security; Health and wellbeing; Housing, communities and neighbourhoods; Labour market; Homelessness; Social Capital; Health; Employment; Diet/Food security; Physical; Social support; Addictive behaviours; Housing, communities and neighbourhoods; Employment and unemployment; Health and wellbeing